2019
DOI: 10.1038/s41893-018-0203-0
|View full text |Cite
|
Sign up to set email alerts
|

Larger gains from improved management over sparing–sharing for tropical forests

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 48 publications
2
56
0
1
Order By: Relevance
“…When a landscape that is largely ecologically intact is being 'opened up' for development, strategic, proactive planning is needed to identify opportunities for enhanced outcomes for both environmental and agricultural goals (Forman and Collinge 1997). Systematic planning can help guide complex land-use decisions by fostering stakeholder engagement, improving the efficiency of land use allocation, describing the tradeoffs between biodiversity and economic objectives thereby identifying compromise solutions and, identifying management opportunities and strategies that can improve biodiversity outcomes in production landscapes (Polasky et al 2008, Runting et al 2015, Adams et al 2016, Estes et al 2016, Runting et al 2019, Strassburg et al 2019. However, to date, these efforts typically have been conducted in transformed (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…When a landscape that is largely ecologically intact is being 'opened up' for development, strategic, proactive planning is needed to identify opportunities for enhanced outcomes for both environmental and agricultural goals (Forman and Collinge 1997). Systematic planning can help guide complex land-use decisions by fostering stakeholder engagement, improving the efficiency of land use allocation, describing the tradeoffs between biodiversity and economic objectives thereby identifying compromise solutions and, identifying management opportunities and strategies that can improve biodiversity outcomes in production landscapes (Polasky et al 2008, Runting et al 2015, Adams et al 2016, Estes et al 2016, Runting et al 2019, Strassburg et al 2019. However, to date, these efforts typically have been conducted in transformed (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, whilst the optimal composition of land under alternative management differed between regions, we find some general commonalities. By exploring the full range of scenario space, our study adds to a growing body of research which suggests that mixed strategies, in which high-yield production enables an increase in the area of both 'spared' natural habitat and, elsewhere within same the region, 'shared' low-yield farmland, can outperform both land sharing and two-compartment sparing (Geschke, James, Bennett, & Nimmo, 2018;Law et al, 2017;Runting et al, 2019).…”
Section: In Both Regions Species On Thementioning
confidence: 99%
“…Within terrestrial protected areas, for example, Adams et al 16 found that the relative priority of expansion and management is determined by observable factors: the relative costs of the two actions and rates of degradation in protected and unprotected areas. Further, Runting et al 45 found greater biodiversity outcomes from improved management compared to shifting to a landscape-sparing strategy. Similar results were found by Kuempel et al 44 in the marine context where optimal budget allocations were split across enforcement or expansion, but the long-term allocations favored enforcement, and by McGowan et al, 46 who found that small management budgets favor marine protected area establishment, whereas larger budgets favor fisheries management strategies.…”
Section: Guidelines For Achieving Aichi Target 11 Objectivesmentioning
confidence: 99%